동종 조혈모세포이식 후 발생한 안구 이식편대숙주병의 임상 양상과 위험인자에 대한 분석 - 이민규; 배지현; 임동희; 정의상; 정태영,Min Gyu Lee, MD, Gi Hyun Bae, MD, Dong Hui Lim, MD, Eui Sang Chung, MD, PhD, Tae Young Chung, MD, PhD (Daihan angwa haghoi jabji, 2014)
목적: 동종 조혈모세포이식을 받은 환자에서 안구 이식편대숙주병(GVHD)의 발생과 임상 양상, 위험인자 및 생존율에 대해 분석하였다. 대상과 방법: 동종 조혈모세포이식을 받고 안과에 방문한 환자 99명의 의무기록을 후향적으로 분석하였다. 세극등현미경 검사로 안구GVHD의 발생 여부를 살펴보고, 그에 따른 각 군의 임상적 특징과 생존율을 비교하였다. 그리고 안구 GVHD의 발생과 관련 있는위험인자에 대하여 분석하였다. 결과: 99명 중 38명(38.38%)에서 동종 조혈모세포이식술 후 평균 315일 후에 안구 GVHD가 발생하였다. 안구 GVHD로 진단된 38명중 22명(57.88%)은 건성안만을 보였고, 16명(42.11%)은 결막질환이 동반되었다. 위험인자 분석에서 타장기 GVHD의 발생 여부(hazard ratio (HR) 35.76, p<0.001)와, 침범 개수(HR 3.07, p<0.001)에 따라, 특히 피부(HR 2.31, p=0.029), 구강(HR 8.16, p<0.001),소화기(HR 5.00, p=0.002)를 침범한 경우 안구 GVHD의 발생률이 높았다. 경과관찰 기간 중 결막질환이 있는 군이 안구 GVHD가없는 군 및 건성안 군과 비교하여 생존율이 낮았으나 통계적으로 유의하지는 않았다(log rank test, p=0.208). 결론: 동종 조혈모세포이식 후 안구 GVHD는 빈번히 발생하고 상당수가 만성기에 발생하였다. 또한 타장기 GVHD의 발생과 그 개수,특히 피부, 구강, 소화기의 침범은 안구 GVHD의 발생에 영향을 미칠 수 있을 것으로 생각한다. Purpose: To investigate the incidence, clinical manifestations, and risk factors of ocular graft-versus-host disease (GVHD) aswell as the survival of the patients after allogeneic hematopoietic stem cell transplantation (HSCT). Methods: The medical records of 99 patients who visited our clinic and were screened for ocular GVHD after allogeneic HSCTwere reviewed retrospectively. Subjects were divided into 2 groups depending on the occurrence of ocular GVHD on slit-lampbiomicroscopy. We compared clinical manifestations and survival between the 2 groups and analyzed the risk factors associatedwith the development of ocular GVHD. Results: Ocular GVHD was diagnosed in 38 patients (38.38%) at a mean of 315 days after HSCT. Out of the 38 patients who developedocular GVHD, 22 patients (57.89%) were diagnosed with dry eye only and 16 patients (42.11%) were diagnosed withconjunctival disease. The presence of extraocular GVHD (hazard ratio (HR) 35.76, p < 0.001), the number of extraocular GVHD(HR 3.07, p < 0.001), skin GVHD (HR 2.31, p = 0.029), oral GVHD (HR 8.16, p < 0.001), and gastrointestinal tract GVHD (HR5.00, p = 0.002) were independent risk factors of ocular GVHD. Comparisons of the survival demonstrated decreased survival ofpatients with conjunctival disease compared to patients without ocular GVHD and patients with dry eye only, but there was nostatistically significant differences (log rank test, p = 0.208). Conclusions: Ocular GVHD is common after allogeneic HSCT. The majority of ocular GVHD occurs in the chronic stage and isassociated with decreased survival. Therefore, more intensive and long-term follow-up with ophthalmic and systemic monitoringis necessary, especially in patients who have extraocular GVHD, for early recognition and proper treatment of ocular GVHD. KCI Citation Count: 1